Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/ecy.3712
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of richness, abundance, and turnover in mountain bumble bees and their floral hosts

Abstract: Environmental gradients generate and maintain biodiversity on Earth. Mountain slopes are among the most pronounced terrestrial environmental gradients, and the elevational structure of species and their interactions can provide unique insight into the processes that govern community assembly and function in mountain ecosystems. We recorded bumble bee–flower interactions over 3 years along a 1400‐m elevational gradient in the German Alps. Using nonlinear modeling techniques, we analyzed elevational patterns at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…Olympus, specifically unimodal clinal patterns for bumblebees and hoverflies due to their ability to cope with high‐altitude low temperatures (McCabe & Cobb, 2021; Peters et al, 2016); this is in line with their α‐diversity patterns found in previous studies on mountains around the world (Table 1, lines 10–14, 18–19). Studies on elevational patterns of β‐diversity of pollinators have always shown a linear increase, usually deriving from the high turnover component (Table 1, lines 2, 6, 8, 13; but see line 4 for the prevalence of nestedness component); besides, a meta‐analysis considering different organisms and ecosystems also showed prevalence of the turnover component (Soininen et al, 2018). In addition, studies on β‐diversity of interactions were also found high turnover component (Encinas‐Viso et al, 2022; Simanonok & Burkle, 2014; Sponsler et al, 2022). We predict that this will be also the case in Mt.…”
Section: Introductionmentioning
confidence: 99%
“…Olympus, specifically unimodal clinal patterns for bumblebees and hoverflies due to their ability to cope with high‐altitude low temperatures (McCabe & Cobb, 2021; Peters et al, 2016); this is in line with their α‐diversity patterns found in previous studies on mountains around the world (Table 1, lines 10–14, 18–19). Studies on elevational patterns of β‐diversity of pollinators have always shown a linear increase, usually deriving from the high turnover component (Table 1, lines 2, 6, 8, 13; but see line 4 for the prevalence of nestedness component); besides, a meta‐analysis considering different organisms and ecosystems also showed prevalence of the turnover component (Soininen et al, 2018). In addition, studies on β‐diversity of interactions were also found high turnover component (Encinas‐Viso et al, 2022; Simanonok & Burkle, 2014; Sponsler et al, 2022). We predict that this will be also the case in Mt.…”
Section: Introductionmentioning
confidence: 99%
“…Albeit CHC profiles and climate-associated chemical traits did not change systematically along the elevational gradient in B. pascuorum, we detected a decline in trait variance: Individuals collected in high elevations-especially above the tree line-differed less in the proportion of saturated components than individuals from low-or mid-elevations. A similar reduction of trait variation with elevation, and with the tree line as potential threshold, was detected in other functional traits, including bumble bee tongue length (Sponsler et al, 2022b) and wild bee body size (Classen et al, 2017). Pronounced environmental filtering at habitats with less variable microclimatic conditions (Hoiss et al, 2012) might cause such declines.…”
Section: High Intraspecific Chc Variation and Potential Environmental...mentioning
confidence: 58%
“…Alpine bumble bees (Apidae: Bombus) are the most efficient and widespread pollinators in temperate mountains (Bingham and Orthner, 1998;Gorenflo et al, 2017). Within the genus Bombus, species differ substantially in their preferred elevational niche (Rasmont et al, 2015;Minachilis et al, 2020;Sponsler et al, 2022a), with few species being restricted to the cool and exposed conditions above the tree line. Within a species, populations and individuals can face substantial differences in their climatic environments along mountain slopes or during foraging flights under the typically fluctuating weather conditions of the mountains (Sponsler et al, 2022a), occasionally, when the cloud cover shifts abruptly, within minutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a genus level, they encompass wide geographic ranges, with diverse hotspots in both cool mountainous regions and high temperate latitudes ( Williams, 1998 ), but also with several species in the Neotropics and Southeast Asia ( Michener, 2007 ). In temperate mountains like the Alps, many, but not all, species have broad elevational distributions and cope with climatically heterogeneous environments ( Sponsler et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%